Pengaruh Penggunaan Serial Animasi Terhadap Perkembangan Sosial Emosional Pada Anak Usia 5-6 Tahun Di TK Kartika - Sheila, Sheila Amelia Maulida; Kristianty Wardany, Diny; Hidayanti, Maria (Indonesian Journal of Islamic Education, 2024)
This research is based on a problem that shows that children's social-emotional skills in children aged 5-6 years at Kartika Kindergarten IX-12 have not been developed. The research method used in this study uses a quantitative research method with the type of experimental research and the research design uses a pre-experimental design with the form of research design used, namely one-group pretest-posttest design. Data collection techniques through observation, interviews, and documentation. The sample population in this study is 15 children and the sample is 15 children. Data processing and data analysis techniques used comparative statistical analysis of paired T tests. The results of the study on social-emotional skills in children aged 5-6 years at Kartika IX-12 Kindergarten, Tenjolayar Village, Cigasong District, Majalengka Regency before the use of animation serial media showed a percentage of 13.33% Undeveloped (BB). 26.67% began to develop (MB). 53.33% Developed as expected (BSH) 6.67% Developed Very Well (BSB). So that there is an increase that shows the majority of the best scores in the Very Good Developing (BSB) category. determining the improvement of social-emotional skills through the "T" test The average value of the pretest count was 38.8667, and the average posttest count increased to 57.8630, thus based on the results of the "T" test, it can be concluded that there is an increase in social-emotional ability which means that there is an influence of the use of animated series on the improvement of social-emotional skills in children aged 5-6 years at Kartika Kindergarten IX-12 Tenjolayar Village, Cigasong District, Regency Majalengka for the 2023/2024 Academic Year.